Analisis Kesalahan Siswa Dalam Menyelesaikan Soal Cerita Matematika - Kahar, Muhammad Syahrul; Layn, Muhamad Ruslan (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2017)
The objectives of this research are: (1) To know kind and error place that made of students grade VIII SMP PGRI Kota Sorong in finishing story match question on relasion material. (2) To know what factors that made students grade VIII SMP PGRI Kota Sorong did error in finishing story match question on relasion material.This study is qualitative Researchbecause the data collect and explain in word form that arrange in the sentences and it is not numeric or value form. This research aim to get deep description and collect information detail about errors that made of students in finishing story match question based on data which is gotten in the research field, and approach that used to analyze in form of text. The conclusions of this study are as follows: (1) Kinds of students’ error of grade VIII SMP PGRI Kota Sorong in finishing story match question on relation material as follow: a) error in understanding and comprehending command question, presentation of students’ error made by 14 students in this error is 73,7%. b) Error in finishing question. Error’s persentation that made by 16 students in this error are 84,2%. c) students’ error who did not answer the question. Error presentation that made by 13 students in this error are 68,2%. (2) caused students’ error of grade VIII SMP PGRI Kota Sorong in finishing stoty ,atch question on relation material as follow: a) error in stating diagram arrow. b) Error in stating diagram cartesius. c) Error in stating the state of sequential pairs.